DETERMINANTS OF THE DEVELOPMENT OF START-UP UNDERTAKINGS IN THE CONTEXT OF ECONOMIC SECURITY OF POLISH ECONOMY - Kaliszczak Lidia; Kozioł Karolina (2020)
The study focuses on the problem of determinants of the development of start-up undertakings in Poland in the context of ensuring economic security. It analyses the term start-up, assesses the condition and directions of start-up business activity and discusses the actions taken in order to create the so called start-up environment in selected Polish cities. Identification and analysis of the determinants of start-up undertakings have been conducted with a division into internal ones, relating to the subjectivity of the entrepreneur and his role in the economy, and external ones, which generally comprise the human and social capital, legal regulations, institutional environment and financing. It is argued that the primary source of entrepreneurial behaviour are internal determinants in contrast to external ones, such as legal regulations or sources of financing.